369 The Burnout Pandemic; the Effect of Socioeconomic Status and Training Programmes on Burnout in Postgraduate Trainees in the United Kingdom. (28th February 2022) - Super, J.; Gunnee, M.; Little, M.; Vinnicombe, Z.
Abstract: Introduction: Burnout is described as a state of mental exhaustion caused by one's professional life, and is characterised by three domains: emotional exhaustion, depersonalisation, and a reduced sense of accomplishment. The prevalence of stress is high amongst doctors, and varies by specialty, gender, trainee level, and socioeconomic status. The authors set out to examine the scale of the problem, as well as to determine the influence of both socioeconomic status and chosen training programme on burnout amongst postgraduate trainees. This would identify at risk groups, and aid in future targeted interventions. Method: Cross-sectional data was obtained, following approval from the General Medical Council (GMC), from The National Training Survey, completed annually by all trainees in the United Kingdom. Data was then anonymised and analysed. Burnout scores were derived from the Copenhagen Burnout Inventory and are positively framed (higher scores equal lower burnout). Results: The questionnaire was completed by 63, 122 participants across 2019 and 2020. Mean burnout amongst all trainees combined was 52.40 +/- 19.29. Burnout scores from the most deprived quintile was significantly lower compared with those from the least deprived quintile; 51.02 +/- 20.64 versus 52.89 +/- 18.92 respectively (p < 0.001). The highest levels of burnout were reported in Internal Medical Training, Emergency Medicine, Obstetrics and Gynaecology, and Core Surgical Training respectively. Conclusions: Postgraduates from lower socioeconomic backgrounds are more likely to encounter burnout during training. At risk groups who may also benefit from targeted intervention include Core Surgical Trainees, requiring further examination through future studies.